2016
DOI: 10.1177/1090198116679359
|View full text |Cite
|
Sign up to set email alerts
|

Pairing Animal Cartoon Characters With Produce Stimulates Selection Among Child Zoo Visitors

Abstract: In order to address the pervasive trend of underconsumption of fruits and vegetables among children, we examined the hypothesis that children would be more likely to select fruits (apple slices, bananas, and oranges) and vegetables (baby carrots) when paired with animal cartoon image than when available without the character image. Tested in a randomized experiment using counterbalancing, products were arranged on two tables at two separate family fun nights held at a local zoo. Animal character produce paring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In partnership with a local urban zoo (54,319 annual visitors) researchers implemented a marketing intervention using zoo animal characters (Tastimals), which were developed and pilot tested in an earlier phase of the work. 21 In the previous phase, the research team examined whether children would be more likely to select healthy products (e.g., fresh fruit) when the product was paired with a Tastimals character than when available without the character image. 21 In the prior study 2 Tastimals character images, the Tamarin and Green Iguana, were randomly paired with free fresh fruit during a Family Fun Night.…”
Section: Approach and Research Designmentioning
confidence: 99%
See 3 more Smart Citations
“…In partnership with a local urban zoo (54,319 annual visitors) researchers implemented a marketing intervention using zoo animal characters (Tastimals), which were developed and pilot tested in an earlier phase of the work. 21 In the previous phase, the research team examined whether children would be more likely to select healthy products (e.g., fresh fruit) when the product was paired with a Tastimals character than when available without the character image. 21 In the prior study 2 Tastimals character images, the Tamarin and Green Iguana, were randomly paired with free fresh fruit during a Family Fun Night.…”
Section: Approach and Research Designmentioning
confidence: 99%
“…21 In the previous phase, the research team examined whether children would be more likely to select healthy products (e.g., fresh fruit) when the product was paired with a Tastimals character than when available without the character image. 21 In the prior study 2 Tastimals character images, the Tamarin and Green Iguana, were randomly paired with free fresh fruit during a Family Fun Night. Findings showed that significantly more products paired with a character were selected (62.38%) than the same products not paired (37.62%), χ2 = 46.32, df = 1, p < .001.…”
Section: Approach and Research Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, nudging operates directly on behaviors rather than attitudes and knowledge (here, we rely on the three-way split outlined in Steckler et al., 1995). Focusing on behavior is significant, as engendering health-protective behaviors has been described as the main concern of health promotion (Karpyn et al., 2017; Simons-Morton, 2012). A third potential advantage of public health nudging relates to Thaler and Sunstein’s (2008) insistence that unlike legislating for better public health, nudging interventions preserve individuals’ autonomy.…”
mentioning
confidence: 99%